Factors affecting long term results of successfully treated amblyopia: initial visual acuity and type of amblyopia. Issue 3 (March 1995) - Levartovsky, S; Oliver, M; Gottesman, N; Shimshoni, M
Abstract : AIMS–The study aimed to assess the effect of initial visual acuity and type of amblyopia on the long term results of successfully treated amblyopia. METHODS–The visual acuity of 94 patients, who had been successfully treated for unilateral amblyopia by occlusion of the good eye and followed up to the age of 9 years, was examined 6.4 years, on average, after cessation of treatment. Patients were divided into two groups according to the depth of amblyopia before occlusion therapy was started: those with visual acuity between 20/60 and 20/100 and those with visual acuity of 20/100 or worse. RESULTS–Deterioration of visual acuity was observed in 42% of patients in the first group and in 63% of patients in the second group. Their average deterioration, as measured by the Snellen chart, was 0.58 and 1.54 lines, respectively. The results were also assessed by the division of patients into three groups according to the type of amblyopia: strabismic, strabismic anisometropic, and anisometropic. Deterioration of visual acuity occurred in 46%, 79%, and 36% of patients in these three groups, with an average deterioration on the Snellen chart of 0.70, 2.04, and 0.64 lines, respectively. CONCLUSION–It is concluded that low initial visual acuity and strabismic anisometropic amblyopia are risk factors for deterioration of visual acuity in the long term, following the successful earlier treatment of eyes with amblyopia.